Foodborne illnesses in Brazil: control measures for 2014 FIFA World Cup travellers - Ana Carolina Ritter; Eduardo Cesar Tondo (Journal of Infection in Developing Countries)
Foodborne diseases are typically caused by the ingestion of food contaminated with micro-organisms or their toxins, resulting in gastrointestinal disorders and in some severe cases hospitalization and death. In Brazil, foodborne illnesses are caused mainly by Salmonella, Staphylococcus aureus and Escherichia coli. The most important contributing factors for outbreaks are exposure of foods to unsuitable temperatures, inadequate food preparation and contamination of raw material or water used to prepare food. Recently, aiming to prevent foodborne illnesses during the 2014 FIFA World Cup, Brazil has developed a risk-based evaluation tool able to assess and grade Brazilian food services in cities that will host football matches. This tool has been used by the Brazilian sanitary surveillance officers during the inspection of facilities where food services. This is considered an innovative preventative sanitary action because it was created based on scientific information, statistical calculation and on risks of foodborne diseases occurrence. In this mini-review we summarize general data, control measures and how travellers can prevent foodborne illness in Brazil during the 2014 FIFA World Cup.